Risk of eating disorders and its association with expectations of thinness, body satisfaction and body mass index in Turkish university students: A cross-sectional study: Eating Disorders, Expectations of Thinness, and Body Satisfaction - Günal, Ahmet Murat; Karlı, Kevser; Öngün Yılmaz, Hande (Progress in Nutrition, 2023)
Background and aim: Eating disorders are a diagnostic group characterized by the desire to be thin, excessive fear of obesity, and severely impaired body satisfaction. This study aimed to determine university students' risk of eating disorders and their relationship with the expectation of thinness, body satisfaction, and body mass index (BMI).Methods: The cross-sectional study was conducted with 535 (Female: 478, Male: 57) participants studying at the faculty of health sciences of two universities. Students were randomly selected according to their university, department, and gender using a stratified sampling method. Data were collected using the information form, Eating Attitude Test Short Form (EAT-26), Interpersonal Outcome Expectancies for Thinness (IOET), and  Body Satisfaction Scale (BAS).Results: Participants' mean EAT-26 scores were 10.97 (SD=9.99), IOET-TR scores 10.97 (SD=9.99), BAS scores 35.08 (SD=7.47). It was found a positive correlation between EAT-26 and IOET-TR (r=0.141, p=0.001); negative correlation between EAT-26 and BAS (r=-0.228, p